MADE AZUSA: uma abordagem histórica e multiculturalista da construção da identidade das Assembleias de Deus no Brasil de 1911 a 1932. - Silva, Jonas Euflausino da (2021)
The present study investigates the formation of the identity of the Assemblies of God Pentecostal Churches, in Brazil, in the period between 1911 and 1932, founded by two Swedish missionaries from the American Pentecostal movement. The aforementioned time span for the study was chosen due to being the period in which the founders effectively performed their leadership within the institution. The Brazilian Assemblies of God are included in the category of Pentecostal churches, which were formed from processes of cultural hybridism, originated in the Christianization of enslaved Africans in the United States, eventually leading to the establishment, in 1906, of a mission on Azusa Street in Los Angeles. This mission was led by a son of a former enslaved couple, named William J. Seymour, who then promoted a missionary action that propagated the movement to the world. Taking as an investigative source the historical documents and bibliographic surveys pertaining to the origin and foundation of Pentecostalism and the Assemblies of God in Brazil, the present research deepens the debate on the origins and history of that church denomination in the Brazilian context, thus seeking to understand the denomination’s identity, having as theoretical framework the concept of identity and cultural hybridism developed by Stuart Hall, Homi Babha, and Néstor Garcia Canclini. The analysis undertaken is based on the understanding of multiculturalism in the formation of hybrid cultural identities and, consequently, in the constitution of the Brazilian Assemblies of God identity.